The impact of excessive body weight on postural balance - Pankanin, Ewelina Stefania (Journal of Education, Health and Sport, 2018)
Body balance is the determinant of efficient human functioning in daily activities. The equilibrium system is a complex system that draws information about the position of the body in space and the relative position of the body parts relative to one another from the balance organ, proprioceptors and the visual system. Due to the multidimensionality of the balance system, many factors can affect its operation and disrupt the efficiency of work. Excessive weight due to the different distribution of excess body fat may disturb balance control. In addition, in the states of overweight and obesity, the muscles that are responsible for maintaining the vertical posture are very often weakened.